FOREIGNISASI LEKSIKON BUDAYA DALAM PENERJEMAHAN RONGGENG DUKUH PARUK KE DALAM BAHASA JEPANG - Nishfullayli, Sa’idatun (Universitas Diponegoro, 2017)
In the translation of cultural words, Domestication and Foreignization strategy is a kind of translation strategy that is widely applied by translators. The tendency to use one of these strategies in a translation work can be identified through the analysis of translation techniques. This article discusses the translation strategy of cultural words in Ronggeng Dukuh Paruk which had translated into Japanese, Parukku Mura no Odoriko. Through the identification and analysis of translation techniques, it is known that the cultural words in Ronggeng Dukuh Paruk is translated into Japanese using several techniques: (1) borrowing, (2) paraphrase, (3) using cultural words which equivalence in target language, (4) using generic words, (5) using neutral words . From the results of calculating the amount of usage of each technique, it is known that the borrowing and paraphrase is the most widely used techniques, so it can be concluded that in this translation used the strategy of foreignization. Foreignization is the strategy that focuses on the source text, as an interpreter attempt to maintain the concept of culture As well as the socio-cultural values of Javanese society as in the original novel. The fact raises the assumption that Parukku Mura no Odoriko lacks the tastes of readers in Japan because of the many foreign cultural concepts in the novel thus making the distance between the reader and the translation product itself. <a href=